Halal tourism dynamics: The impact on tourist satisfaction at Padang beach attractions with tourist destination image as an intermediary - Suhira; Wardi, Yunia (Universitas Negeri Padang, 2023)
The purpose of this study was to analyze the impact of halal tourism on tourist satisfaction visiting Padang Beach tourist attractions. Additionally, it examined the effect of halal tourism on the image of tourist destinations and analyzed the influence of a tourist destination image on tourist satisfaction. Furthermore, the study aimed to analyze the effect of halal tourism on tourist satisfaction through the tourist destination image variable as a mediator. The population in this study comprised visitors (tourists) who have visited or are currently visiting Padang Beach tourist attractions. The sampling technique used was purposive sampling, resulting in a sample size of 100 respondents. Data analysis for this study utilized SmartPLS 4.0. The results of the study are as follows: (1) Halal tourism has a positive and significant effect on tourist satisfaction visiting Padang Beach tourist attractions. (2) Halal tourism has a positive effect on the image of tourist destinations at tourist attractions in Padang Beach. (3) The image of tourist destinations has a positive and significant effect on tourist satisfaction. (4) The image of tourist destinations mediates the influence of halal tourism on tourist satisfacti on at tourist attractions in Padang Beach.